Finite element method for optimum design selection of carport structures under multiple load cases - Ozkal, F. M.; Cakir, F.; Arkun, A. K. (UNIV MARIBOR, FAC MECHANICAL ENGINEERING, 2016)
In the field of structural modelling, it is obvious that the number of applicable designs for a particular structural necessity is limitless. Along with the integration of various kinds of available structural materials into this complexity, it gets harder to be able to determine the best design before the production stage. In recent years, with the improvement of computational and structural technology, there have been many studies on the optimal design selection. This study focuses on carport structures and pursuing their best producible shape. For this aim, a performance index formulation was developed to assist the decision of material efficiency as well as structural rigidity. Thereafter, five conceptual models were numerically modelled and finite element analyses (FEA) for multiple load cases were carried out. Reviewing the FEA results, the most appropriate model was determined by the application of this performance qualification method. Results of the analyses show that optimum design of structures under multiple load cases can be determined using finite element method. (C) 2016 PEI, University of Maribor. All rights reserved.
Keywords: Structural producibility; Performance decision; Multiple load cases; Manufacturing; Finite element method; Engineering; Materials Science